MORAL VIRTUES OF NANCY IN CHARLES DICKENS’ OLIVER TWIST - Gasa, Yeremias; Separ, Fransiskus M; Doi, Maksimilianus (Fakultas Hukum dan Sosial Humaniora Universitas Flores, 2022)
This study aimed at knowing what moral virtues are in Nancy’s character and the influence of moral virtues to the main character in Oliver Twist. This study also employed virtue ethics theory with qualitative descriptive design. Source of data were taken from the novel of Charles Dickens, Oliver Twist. The methods of collecting data were by reading, identifying, and writing dialogs relating to the problems of the study. This analysis reveals that Nancy is a good person because she has a moral nature. The criminal environment cannot affect one's disposition. Nancy can maintain her character with her moral virtues that are full of kindness, courage, honesty, and loyalty. With those virtues, Nancy can live righteously and can make decisions in deciding what is good for her and for Oliver's life. Oliver can be free from criminals and get his happiness.